Blackflies (Diptera: Simuliidae) in Croatia: species richness, distribution and relationship to surrounding countries - Ivković, Marija; Kúdela, Matuš; Kúdelová, Tatiana (Zootaxa, 2016)
All records of blackflies (Simuliidae) from the territory of Croatia are summarized, including previously unpublished data. The blackfly fauna of Croatia consists of 28 species. Simulium (Nevermannia) angustitarse (Lundström), Simulium (Nevermannia) cryophilum (Rubtsov) complex, Simulium (Nevermannia) lundstromi (Enderlein), Simulium (Nevermannia) vernum Macquart complex, Simulium (Simulium) argyreatum Meigen, Simulium (Simulium) bezzii (Corti) complex, Simulium paraequinum Puri and Simulium pseudequinum Séguy are reported for the first time from Croatia. Information related to the ecoregions, in which species were found and specific species traits are given. Genus Prosimulium Roubaud is represented by one species only. Genus Simulium Latreille is represented by 27 species in six subgenera, with subgenus Simulium Latreille s. str. being most species rich (13 species) and subgenera Boophthora Enderlein and  Trichodagmia Enderlein represented each by only one species. Compared to the neighboring countries, the Croatian species assemblage is most similar to the fauna of Slovenia and least similar to that of Italy. The relatively low number of species, presence of several species complexes and unclear identity of other species show that further research of blackflies in Croatia is needed.